Stepwise protein-mediated RNA folding directs assembly of telomerase ribonucleoprotein - Stone, Michael D. (2007)
Telomerase is an essential cellular ribonucleoprotein (RNP) that solves the end replication problem and maintains chromosome stability by adding telomeric DNA to the termini of linear chromosomes1–3. Genetic mutations that abrogate normal assembly of telomerase RNP cause human disease4. It is thus of fundamental and medical importance to decipher cellular strategies for telomerase biogenesis, which will require new insights into how specific interactions occur in a precise order along the RNP assembly pathway. Here, we demonstrate a single-molecule approach to dissect the individual assembly steps of telomerase. Direct observation of complex formation in real time revealed two sequential steps of protein-induced RNA folding, establishing a hierarchical RNP assembly mechanism: interaction with the telomerase holoenzyme protein p65 induces structural rearrangement of telomerase RNA, which in turn directs binding of the telomerase reverse transcriptase (TERT) to form the functional ternary complex. This hierarchical assembly process is facilitated by an evolutionarily conserved structural motif within the RNA. These results identify the RNA folding pathway during telomerase biogenesis and define the mechanism of action for an essential telomerase holoenzyme protein.